DETERMINANT OF OPERATIONAL PERFORMANCE: CASE OF PRIVATE HIGHER EDUCATION IN BANTEN - Annisa, Amartya Nadhia; Zulfikar, Rudi; Ismawati, Iis; Rohaeni, Nani (Yayasan Education and Social Center, 2024)
This study aims to determine the effect of intellectual capital and IT capability on operational performance of private higher education in Banten. This study used convenience sampling in which the sample was taken based on who was conveniently available to provide it. The respondents were structural officials from private higher education who taught at universities from the selected sample. The type of data used as primary data. The result for the two independent variables which are intellectual capital as well as IT capability shows that have a positive significant effect on operational performance. The collected data by sending questionnaires to 30 private higher education in Banten with considered could be processed. The data were tested using the SEM-PLS analysis tool through SmartPLS 3.0. The results of this study are expected to be used for other private higher education in relation to the importance of intellectual capital and IT capability for an institution and its effect on their operational performance